Importance of the anchor group position (para versus meta) in tetraphenylmethane tripods: synthesis and self-assembly features - Lindner, Marcin; Valášek, Michal; Homberg, Jan; Edelmann, Kevin; Gerhard, Lukas; Wulfhekel, Wulf; Fuhr, Olaf; Wächter, Tobias; Zharnikov, Michael; Kolivoška, Viliam; Pospíšil, Lubomír; Mészáros, Gábor; et al. (Chemistry - a European journal, 2016)
Abstract The efficient synthesis of tripodal platforms based on tetraphenylmethane with three acetyl-protected thiol groups in either meta or para positions relative to the central sp3 carbon for deposition on Au (111) surfaces is reported. These platforms are intended to provide a vertical arrangement of the substituent in position?4 of the perpendicular phenyl ring and an electronic coupling to the gold substrate. The self-assembly features of both derivatives are analyzed on Au (111) surfaces by low-temperature ultra-high-vacuum STM, high-resolution X-ray photoelectron spectroscopy, near-edge X-ray absorption fine structure spectroscopy, and reductive voltammetric desorption studies. These experiments indicated that the meta derivative forms a well-ordered monolayer, with most of the anchoring groups bound to the surface, whereas the para derivative forms a multilayer film with physically adsorbed adlayers on the chemisorbed para monolayer. Single-molecule conductance values for both tripodal platforms are obtained through an STM break junction experiment.
Gesehen am 03.06.2020